2021
DOI: 10.1002/hpja.451
|View full text |Cite
|
Sign up to set email alerts
|

“They don't think it will ever happen to them”: Exploring factors affecting participation in alcohol‐influenced aquatic activity among young Australian adults

Abstract: Issue addressed: Young adults are over-represented in alcohol-related drownings in high-income countries; however, little research has investigated their behaviours and decision-making to inform prevention efforts.Methods: Semi-structured interviews were conducted with 23 young Australian adults (aged 18-24 years). Questions, informed by previous research, inquired about behavioural practices in aquatic contexts and influences on involvement in alcoholinfluenced aquatic activity. Interviews were transcribed ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Eight studies were published in the last 5 years (since 2018) [6, 10, 30–35]. Seven studies used a cross‐sectional survey design [6, 23, 24, 32, 34–36], four used qualitative methods [10, 30, 31, 37], and one was a mixed methods study using interviews and a cross‐sectional survey [33]. The remaining study was a narrative review of literature investigating the notion of ‘dangerous masculinities’ concerning drowning risk among young men [38].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eight studies were published in the last 5 years (since 2018) [6, 10, 30–35]. Seven studies used a cross‐sectional survey design [6, 23, 24, 32, 34–36], four used qualitative methods [10, 30, 31, 37], and one was a mixed methods study using interviews and a cross‐sectional survey [33]. The remaining study was a narrative review of literature investigating the notion of ‘dangerous masculinities’ concerning drowning risk among young men [38].…”
Section: Resultsmentioning
confidence: 99%
“…A study of 'Leavers' celebrations in WA found that while most participants (92%) were aware of the risks of combining alcohol and aquatic activities, only 17% of those who had consumed alcohol around water identified the activity as risky [34]. Some activities were associated with an increased risk, including activities in open (e.g., ocean) rather than closed water (e.g., pools), proposed by the authors as likely due to the perceived predictability [37], control, and familiarity of the latter [31]. Further, activities involving greater alcohol consumption were seen as higher risk [31].…”
Section: Perceptions Of Riskmentioning
confidence: 93%
See 3 more Smart Citations